An Analysis of Factors Influencing Low Enrolment and Retention of Girls with Disabilities in Integrated Primary Schools in Embu County, Kenya - Muthoni, Njeru Idah; Otube, Nelly; Ondigi, Samson Rosana (Journal of the American Academy of Special Education Professionals, 2016)
This study investigated the factors that influenced low enrolment and retention rates of girls with disabilities in integrated primary schools. It further explored possible intervention measures that may be employed to mitigate the situation. The study was conducted in selected schools in Runyenjes (Embu East) and Manyatta (Embu North) sub-counties in Embu County. The location was purposely chosen in order to enable the researcher easy access to the respondents. Factors that limit enrollment and retention of girls with disabilities were worth investigating because the government of Kenya provides free primary education for all school going age children although the program does not address fully the education of children with special needs. Questionnaires, interview schedule and focus group discussion (FGD) were the tools adopted for data collection. The data collected were qualitatively and quantitatively analyzed; that is, thematically and frequencies and percentages. Poverty, long distances to school, negative attitude, time wasted by teachers, drug and substance abuse, security, household chores, boy preference, pregnancies and early marriages were the factors established to influence enrollment and retention of girls with disabilities in school.